Optimization Formula of Collagen Nanoemulgel from WasteMilkfish (Chanos chanos) Bones as Antiaging - Nasyanka, Anindi Lupita; Tiadeka, pemta; Nur Imtihani, Hilya; Octaviary, Niken Laras; Prastiyo, Danu (Sainteknol : Jurnal Sains dan Teknologi, 2024)
Climate change has negative impacts throughout the countries in the world, especially Indonesia, which has a tropical climate. Successful aging can be achieved by building individual self-confidence through prevention and skin aging. Indonesia is a producer of milkfish waste, reaching 5.4 tons/year, which is in line with the increasing center of "Otak-otak" milkfish souvenirs found in Gresik. The waste, especially fishbones, can be synthesized into collagen. The characteristic fishbone collagen waste are in the form of large porous sheets, while particle size is an essential factor in the absorption effectiveness of cosmetics. Therefore, Nanoemulgel is able to overcome this problem. This research aims to produce best collagen nanoemulgel from milkfish bone by physical evaluation with varying ratios of surfactant: cosurfactant in collagen nanoemulgel. The research method was done experimentally by comparing the components Tween 80: PEG 400 F1 (30:30), F2 (40:20), and F3 (35:15) through qualitative and quantitative physical characteristics using one-way anova. Evaluations whose results differ significantly are pH on the 7th day, spreadability, and viscosity. Research results show F2 is the best formula and meets physical stability specifications : particle size 3.89 nm, PDI 0.1906, zeta potential -0.2 mV, pH 4.7±0.04, viscosity 890.1± 4.26 cps, spreading 5.93±0.23 cm.